Gambaran Infeksi Telur Cacing Soil Transmitted Helminths Pada Petani Bunga - Oktaviani Windy Safitri; Ririh Jatmi Wikandari (Poltekkes Kemenkes Semarang, 2019)
STH infection is an infection transmitted by intestinal nematodes through the soil. Flower farmers are one of the most vulnerable jobs infected with STH eggs because this work is directly related to the soil. Most of the work as flower farmers is in the Bandungan area because the area is suitable for flower plantations. The purpose of study to describe Soil Transmitted Helminths infection on flower farmers in Jetis Village, Bandungan Subdistrict, Semarang. This study was descriptive observational (non-experimental) research using cross sectional approach. Samples studied were 23 respondents. Feces examination conducted on 23 samples obtained 1 sample (4,3%) infected STH eggs of hookworm species and 22 samples (95,7%) not infected STH eggs. Only 1 flower farmer (4,3%) from 23 flower farmers in Jetis Village, Bandungan Sub-district was infected by Soil Transmitted Helminths egg.